(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The purpose of the study was to assess Performance Management Systems and Service Delivery in Lusaka’s Public Hospitals, challenges and prospects with a focus on employees’ awareness in the implementation of Performance Management systems. The study used a mixed method approach on a sample of 95 selected through simple random and purposive sampling technique. Data were collected using a questionnaire and an interview guide. The findings revealed that employees understood performance management systems for purposes of annual performance review and identification of development needs and training, coupled with facilitation of promotion, although it was moderately implemented. However, challenges to Performance Management Systems included resistance of employees to be appraised, lack of staffs to perform appraisal on others, not knowledgeable on appraisal procedures and feedback. The implications of these findings are that the Ministry of Health through its Human Resource Management and Policymakers should prioritize addressing these challenges through targeted interventions to foster a cohesive PMS framework and performance outcomes that align with the expectations of the workforce. The study recommends that the Human Resource Department should not conduct appraisals for the sake of annual review but should take seriously the recommendations and outcomes of the process in order to improve service delivery.